DIVERSI DALAM UPAYA MEMBERIKAN PERLINDUNGAN TERHADAP ANAK YANG BERHADAPAN DENGAN HUKUM UNTUK MEWUJUDKAN KEADILAN RESTORATIF - SATRIANA, MADE WAHYU CHANDRA (Kerta Dyatmika, 2015)
ABSTRACTÂ Treatment of children in conflict with the law receive special treatment that is certainly different from the treatment of adults who are in trouble with the law. The process of diversion of children in conflict with the law in the society, in order to achieve restorative justice to ensure and protect children and their rights in order to live, grow, develop and participate optimally in accordance with human dignity, as well as protection from violence and discrimination.Â